Recruitment Process Assessment at a Specific Company - Kopecká, Kristýna; Křečková Kroupová, Zuzana, 1972-; Bilavčíková, Irena; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This bachelor thesis is focused on the recruitment process assessment at a specific company from the ICT industry. The theoretical part researches theoretical approaches to extended recruitment processes such as recruitment and hiring, the induction or the employee life-cycle within the company from various literature sources. The practical part consists of a research based on semi-structured interviews with the current employees of the company and their experiences with the company's extended recruitment processes. In the end, the thesis focuses on the comparison of the theory with current trends on the labor market and the practice. Finally, it provides reasonable recommendations of improvements of the recruitment process to the specific ICT company.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses